1998
DOI: 10.2214/ajr.171.4.9762976
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of tears of discoid lateral menisci.

Abstract: OBJECTIVE. The purposeof this study was to determinethe positivepredictivevalue (PPV) for diagnosis of discoid lateral meniscal tear using MR imaging and to describe various patterns of such tears in the knee.SUBJECTS AND METHODS. MR reportsof 77 patients(10â€"67 yearsold) who under went prospective MR imaging that led to a diagnosis of discoid lateral meniscal tear were cor related with arthroscopic results. MR images obtained in 71 patients confirmed to have discoid lateral meniscial tear were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 19 publications
3
26
1
1
Order By: Relevance
“…Grade 1 and grade 2 lesions indicate mucinous or mucoid intrasubstance degenerative change and are usually encountered after 3 or 4 decade. Due to prominent vascularity in children and young adults misinterpretation as grade 1 or 2 tear is usual [4] [11] . Classification of tears: 1.…”
Section: Internal Derangement Of Knee -Mrimentioning
confidence: 99%
“…Grade 1 and grade 2 lesions indicate mucinous or mucoid intrasubstance degenerative change and are usually encountered after 3 or 4 decade. Due to prominent vascularity in children and young adults misinterpretation as grade 1 or 2 tear is usual [4] [11] . Classification of tears: 1.…”
Section: Internal Derangement Of Knee -Mrimentioning
confidence: 99%
“…Magnetic resonance imaging can accurately show a discoid meniscus and reveal a tear. Its positive value in diagnosing discoid lateral menisci has been reported as 92%15). A study by Ryu et al15) involving 77 knees with MRI findings of lateral discoid meniscus tear stated that the most common type of discoid lateral meniscus tear was peripheral tear with horizontal tears.…”
Section: Discussionmentioning
confidence: 99%
“…Smillie theory states that menisci exist as cartilaginous disc at an early stage in the development and congenital discoid meniscus is attributable to the persistence of the disc shape at varying stages of embryonic development, whereas Kaplan postulated in 1974 that discoid menisci are acquired after birth and are related to congenital alteration in the attachment of the meniscus posterior horn by the meniscofemoral ligament thus making it a pathologic entity rather than a congenital anomaly [2]. Anatomical studies by Clark and Ogden have demonstrated that anterior extensions from both menisci to anterior cruciate ligaments can be present after birth [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is an extremely rare anomaly with an incidence of 0.1-0.3% [2]. Only 35 cases have been reported in literature so far [3].…”
Section: Introductionmentioning
confidence: 99%